The desert shall blossom and produce ....tomatoes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Two Israeli scientists have proved that tomatoes can be grown on sand with saline water irrigation, and that there need be no reduction in yield. Professor Dov Pasternak and Joel de Malack have used the vast saline aquifers deep under the Negev...